The role of NEAT1 lncRNA in squamous cell carcinoma of the head and neck is still difficult to define - Kozłowska, Joanna (Contemp Oncol (Pozn), 2020)
INTRODUCTION: Nuclear paraspeckle assembly transcript 1 (NEAT1) is considered an oncogene in various cancers, but the role in head and neck squamous cell carcinomas (HNSCC) is not clear. MATERIAL AND METHODS: Expression of NEAT1 in HNSCC patients’ samples and cell lines was analysed using qRT-PCR. The TCGA expression data of NEAT1 were analysed depending on the clinicopathological parameters and tumour localisation. Correlation and gene set enrichment analysis (GSEA) were conducted, and the results were analysed using the REACTOME and GeneMANIA tools. All statistical analyses were carried out using GraphPad Prism 5 and Statistica 13. RESULTS: The NEAT1 was up-regulated in some patients’ samples and HNSCC cell lines. Moreover, TCGA data analysis indicated that the expression of NEAT1 was up-regulated in tumour tissue in most of the analysed TCGA cancers, including HNSCC. There were no significant differences in levels of NEAT1 between various tumour localisations. Overall survival of individuals with high expression of NEAT1 was slightly longer than in the low-expression group (p = 0.0553). Analysis of genes that positively and negatively correlated with NEAT1 indicated that they are involved in mRNA metabolism and cellular transport. Moreover, the GSEA revealed that in patients with low NEAT1, the most up-regulated genes were in clusters associated with the cAMP-dependent pathway, the MYC pathway, unfolded protein response, the MTORC1 signalling pathway, oxidative phosphorylation, and DNA repair. CONCLUSIONS: Patients with low expression of NEAT1 display worse overall survival, presumably due to up-regulation of certain oncogenic signalling pathways that are important for cancerogenesis.